REPRODUCTIVE CYCLE AND CHANGES IN ASSOCIATED PARTS OF GONAD IN CRASSOSTREA (SACCOSTREA) GLOMERATA (GOULD) FROM THE COAST OF KARACHI - Asif, M (Indian Journal of Fisheries, 2011)
A study of the reproductive cycle of Crassestrea (Saccostrea) glomeratafrom the coast of Karachi is described for the years 1971-73. The species attainsmaturity of gonad in majority of specimens in April, which is continued in fluctuatingmanner through October. Active spawning continues from MaylJune toNovember. Comparison among the different size groups shows that spawning inyoungest size group is very restricted, which may be attributed to abundance ofphagocytes throughout the year. No 'inactive phase' is observed but 'indifferentphase' generally occurs in winter. Comparison with the same Sipecies of NewZealand shows that the temperature range at which reproduction is carried out isdifferent from that of the latter locality, suggesting acclimatisation to differenttemperature condition of the two areas. Glycogen granules were abundant in winterwhich declined gradually reaching minimum value in May|June and this conditionremained in summer. In September, build of glycogen starts, which attained maximumconcentration in the body parts in winter (November through January). Inconclusion the observations on the reproductive cycle of the species from Karachishows a different pattern from those of temperate regions.